Peaceful resistance : advancing human rights and democratic freedoms / advancing human rights and democratic freedoms - Press, Robert M. (Aldershot, England ; Burlington, VT : Ashgate, 2006)
"An innovative study that examines how peaceful, domestic tactics by individual human rights activists and organizational activists, with public support, can force an authoritarian regime to make key concessions. Robert Press explores the creation and impact of a culture of resistance. He examines how domestic pressure can be more important than foreign pressure for political reform, especially in underdeveloped, authoritarian states. This study of contemporary Kenya fills in a gap in traditional social movement theory to show how a resistance movement actually starts. Contrary to long-dominant theory, the book shows how the initiative for such a movement can come from activists themselves in the face of severe obstacles in society. With its unique findings on the effects of individual activism and peaceful resistance, this book will attract a broad audience in the study and practice of international relations, comparative politics, sociology, interest groups, peace and conflict, and human rights."--Book jacket.
Establishing a culture of resistance : theoretical perspectives -- Repression and resistance in Kenya : historical perspectives -- Knocking at the door : individual activism -- Opening the door : organizational activism -- Entering the Bastille (peacefully) : from resistance to elected power -- Mass public support : a key element in a culture of resistance -- Conclusion -- Appendix A : Methodology -- Appendix B : Human rights treaties in Kenya -- Appendix C : Socio-economic profiles of Kenya -- Appendix D : Repression and torture in Kenya.
Includes bibliographical references (p. [205]-215) and index.
Keywords: Government, Resistance to -- Case studies; Government, Resistance to -- Kenya; Human rights -- Kenya; Democratization -- Kenya; Political activists -- Kenya; Human rights workers -- Kenya; Widerstand; Mau-Mau.; Kenya